Kin recognition in a butterfly: inferences about its heritability. Issue 3 (4th May 2017) - De Nardin, Janaína; Da Silva, Luciana; Araújo, Aldo M.
Abstract : Some animal species are able to recognise their relatives, cannibalising mostly non-kin individuals, as happens with the caterpillars of the butterfly Heliconius erato phyllis . Here, we established a breeding programme where adults had different coefficients of relatedness (r = 0 and r = 0.5; offspring, respectively with F = 0 and F = 0.25). The caterpillars cannibalised or did not cannibalise sibling eggs, which was used to make inferences on the kin recognition inheritance of non-cannibals, and to estimate its heritability. The parents had both cannibal and non-cannibal phenotypes; crosses were done for all combinations of these phenotypes, which were divided into outbred and inbred. Caterpillars were grown in the laboratory until the adult stage, and were classified as cannibal or non-cannibal after a test with three sibling eggs. The results showed that the mean number of non-cannibal siblings, those that recognise their kin, is larger in inbreds, above 60%, regardless of their parents' behaviour. Among non-inbred individuals the mean frequency of non-cannibal siblings was around 38%; these differences were statistically significant. The heritability was estimated by four methods. For F = 0 it was around 0.24 ± 0.11, and for F = 0.25 it was around 0.20 ± 0.17. These results, taken together, were discussed in terms of a threshold character: above this threshold the expression of the non-cannibal phenotype is allowed. As for the low values for heritabilities, they were discussed in terms of the theory of traits relevant to both fitness and the resource allocation priority hypothesis.